Assessment of Therapeutic Benefit and Option Strategy on Intravesical Instillation for Preventing Bladder Cancer Recurrence after Radical Nephroureterectomy in Patients with Upper Urinary Tract Urothelial Carcinoma. (30th May 2022) - Fan, Bo; Teng, Qiliang; Sun, Min; Wang, Yingzi; Wang, Yutong; Lin, Zhe; Wang, Yuchao; Duan, Xu; Zhang, Liren; Chen, Tingyu; Chen, Sishan; Tai, Yu; et al.
Abstract : Objective . Upper urinary tract urothelial carcinoma (UUT-UC) is a very aggressive disease, characterized by 22%–50% of patients suffering from subsequent bladder recurrence after radical nephroureterectomy (RNU). Although the therapy of intravesical instillation is reported to be effective in preventing bladder recurrence, no study had been reported in Northeast China. The findings relating to the clinical effectiveness of intravesical instillation after RNU are somewhat controversial, and the best efficacy and least adverse effects of instillation drugs have not been widely accepted. Here, we aimed at evaluating the efficacy of intravesical instillation for the prevention intravesical recurrence systematically. Methods . In this retrospective cohort study, from October 2006 to September 2017, 158 UUT-UC patients underwent RNU were divided into 4 groups: epirubicin (EPB) instillation group, hydroxycamptothecin (HCPT) instillation group, bacillus Calmette–Guerin (BCG) instillation group, and noninstillation group. Cox univariate and multivariate analyses were employed to identify the risk factors for intravesical recurrence-free survival (IVRFS). The nomogram model was also applied to predict patient outcomes. Subsequently, to evaluate the clinical significance of intravesical instillation comprehensively, several databases including PubMed, Ovid, and Embase were searched and data from published studies with our results were combined by direct meta-analysis. Moreover, a network meta-analysis comparing instillation therapies was conducted to evaluate the clinical efficacy of different instillation drugs. Results . In our retrospective cohort study, the Kaplan–Meier survival curve demonstrated noninstillation groups were associated with worsened IVRFS. Meanwhile, multivariate analysis indicated that intravesical instillation was independent protective factors for IVRFS (hazard ratio [HR] = 0.731). Moreover, calibration plots, receiver operating characteristic (ROC) curves, area under the curve (AUC) values, and the C-index showed the priority of nomogram's predictive accuracy. Next, direct meta-analysis including 19 studies showed that intravesical instillation could prevent the recurrence of bladder cancer with a pooled risk ratio (RR) estimate of 0.53. Subgroup analysis by study type, year of intravesical recurrence, first instillation time, and instillation times also confirmed the robustness of the results. Moreover, intraoperative instillation was associated with a decrease in the risk of bladder recurrence compared with postoperative instillation. Then, a network meta-analysis including 7 studies indicated that pirarubicin (THP) (surface under the cumulative ranking curve [SUCRA] = 89.2%) is the most effective therapy to reduce the risk of bladder recurrence, followed by BCG (SUCRA = 83.5%), mitomycin C (MMC) (SUCRA = 53.6%), EPB (SUCRA = 52.6%), and HCPT (SUCRA = 5.1%) after the analysis of the value ranking. Conclusions . A maintenance schedule of intravesical instillation prevents the recurrence of bladder cancer after RNU in UUT-UC patients effectively. Large, prospective trials are needed to further confirm its value. Compared with other chemotherapy regimens, THP may be a promising drug with favorable efficacy to prevent bladder recurrence. As included studies had moderate risk of bias, the results of network meta-analysis should be applied with caution.